2021
DOI: 10.1111/jocs.16158
|View full text |Cite
|
Sign up to set email alerts
|

Measuring potassium level in packed red blood cells before using: Word of caution for congenital cardiac surgery

Abstract: Background and Aim of the Study Transfusion‐associated hyperpotassemia is a serious complication of packed red blood cell (PRBC) transfusion after congenital cardiac surgery. Our study aimed to identify risk factors and potential preventive measures of transfusion‐associated hyperpotassemia in neonates and infants after congenital cardiac surgery. Methods Pediatric patients who underwent congenital cardiac surgery and need transfusion were enrolled in this prospective study. The potassium concentration of PRBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Some authors have shown that potassium levels in paediatric transfusion, mainly to premature neonates, can induce hyperkalaemia and contribute to bad prognostic after the procedure. Altum et al [22] tested potassium levels in RBCs before using them to prevent hyperkalaemia in cardiac surgery cases, whereas other studies have evidenced that washing RBCs, mainly the irradiated ones, can also be a safe alternative to reduce potassium levels in them [23,24]. Thus, U-RBCs can be more beneficial, since their potassium levels were lower than those of A-RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have shown that potassium levels in paediatric transfusion, mainly to premature neonates, can induce hyperkalaemia and contribute to bad prognostic after the procedure. Altum et al [22] tested potassium levels in RBCs before using them to prevent hyperkalaemia in cardiac surgery cases, whereas other studies have evidenced that washing RBCs, mainly the irradiated ones, can also be a safe alternative to reduce potassium levels in them [23,24]. Thus, U-RBCs can be more beneficial, since their potassium levels were lower than those of A-RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…The other relevant parameter that may induce change in serum potassium is the “shelf age” of the transfused packed cells. Potassium concentration increases with the age of the packed cells [ 6 ].…”
Section: Introductionmentioning
confidence: 99%